2010
DOI: 10.1007/s12223-010-0090-x
|View full text |Cite
|
Sign up to set email alerts
|

Point-of-care salivary microbial tests for detection of cariogenic species — Clinical relevance thereof — review

Abstract: Dental caries is a highly prevalent multifactorial disease that can result in serious health impairment. It was shown that oral bacteria play a significant role in caries development. Point-of-care (POC) salivary microbial tests for detection of cariogenic species have been investigated as a potential tool for caries risk assessment. This review aims to evaluate clinical relevance of these tests in the light of recent scientific evidence. Methodology involved PubMed search using key words salivary microbial te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
16
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 102 publications
1
16
0
1
Order By: Relevance
“…Xerostomia is mentioned in the literature as one of the adverse effects of methylphenidate (23). While some authors have reported that methylphenidate causes dry mouth (24), others have not observed any change in SFR associated with this drug (25).…”
Section: Discussionmentioning
confidence: 99%
“…Xerostomia is mentioned in the literature as one of the adverse effects of methylphenidate (23). While some authors have reported that methylphenidate causes dry mouth (24), others have not observed any change in SFR associated with this drug (25).…”
Section: Discussionmentioning
confidence: 99%
“…Higher levels of Streptococcus mutans and lactobacilli increase the risk of dental caries . S. mutans have specifically been found to be associated with WSL due to their highly cariogenic properties . Saliva samples from orthodontic patients showed increase in overall oral bacteria counts after the placement of orthodontic appliances .…”
Section: Introductionmentioning
confidence: 99%
“…12 S. mutans have specifically been found to be associated with WSL due to their highly cariogenic properties. 13 Saliva samples from orthodontic patients showed increase in overall oral bacteria counts after the placement of orthodontic appliances. 14,15 Following orthodontic treatment and bracket removal, S. mutans levels return to normal levels.…”
mentioning
confidence: 98%
“…Saliva can modulate the process of decay as a rich source of host factors, each of which plays a role in preventing dental caries (7,8). It has been well-documented that saliva secretion and its contents play a significant role in dental health (5,9).…”
Section: Introductionmentioning
confidence: 99%